Online Counterfeit Drugs in Point View of National Laws and Maqashid Sharia - Amoury Adi Sudiro; Siti Farhani; Aris Machmud (Research Synergy Foundation, 2024)
The development of information technology gives two sides of the coin in the dynamic of human life, whether positive or negative. This condition is also pertinent to transactions involving cosmetics and psychotropic substances; without close supervision, it may result in consumer harm. In light of this concern, the present study aims to examine how law reviewing the online spreading of medicines gives law protection. This research uses the normative juridical method with the legislative approach. This research uses a qualitative research method in the form of normative juridical research with a statutory approach regarding Online Counterfeit Drugs and examines the synchronization and consistency of its implementation. The legal sources used are primary and secondary sources relating to Online Counterfeit Drugs guarantees. The data collection technique uses library research by examining references to primary and secondary legal sources. Furthermore, the author investigated and evaluated the efficacy of legal sources. This study was carried out from the perspective of Maqashid al-Sharia. The findings of this study indicate a pressing need for regulations that protect consumers engaging in online transactions, particularly those involving pharmaceuticals, cosmetics, and psychotropic substances. Such regulations are essential to prevent consumer losses by ensuring strict liability for manufacturers if their products cause harm. Additionally, the study highlights the crucial role of pharmacists and the National Agency of Drug and Food Control (BPOM) in overseeing the distribution of drugs and cosmetics prior to their market release.